A passive system approach to increase the energy efficiency in walk movements based in a realistic simulation environment - Lima, José (2010)
This paper presents a passive system that increases the walk energy efficiency of a Humanoid robot. A passive system is applied to the simulated robot allowing the energy consumption to be reduced. The optimal parameters for the passive system depend on the joint and gait trajectories. Final results prove the benefits of the presented system apply. It was optimized thanks to a realistic simulator where the humanoid robot was modeled. The model was validated against a real robot.